2022
DOI: 10.1111/cfs.12978
|View full text |Cite
|
Sign up to set email alerts
|

Realizing the potential of a strengths‐based approach in family support with young people and their parents

Abstract: This paper on a strengths-based approach (SBA) to practice is based on empirical research with stakeholders involved in an intensive support programme for young people at risk and their parents in Ireland. The Youth Advocate Programme (YAP) model provides wraparound support to respond to their needs by focusing on their competencies and their coping skills and building networks of community-based supports.The model includes parents or carers in the suite of support offered by advocates. An SBA to practice has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…Similar programs to increase clinicians’ mental health knowledge and communication skills when responding to families’ psychosocial needs may improve provision of family-centered care in congenital heart settings . The Institute for Patient- and Family-Centered Care advocates for integration of evidence-based patient- and family-centered care content into medical education curriculum through a variety of methods, including didactic classroom education, and a strengths-based approach that maximizes use of individual, family, and community resources to improve health outcomes . It also encourages understanding the diverse experiences and perspectives of patients and families through storytelling, shadowing, simulation exercises, and family-centered rounds, which can promote empathetic communication, cultural sensitivity, and reflective practices among clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Similar programs to increase clinicians’ mental health knowledge and communication skills when responding to families’ psychosocial needs may improve provision of family-centered care in congenital heart settings . The Institute for Patient- and Family-Centered Care advocates for integration of evidence-based patient- and family-centered care content into medical education curriculum through a variety of methods, including didactic classroom education, and a strengths-based approach that maximizes use of individual, family, and community resources to improve health outcomes . It also encourages understanding the diverse experiences and perspectives of patients and families through storytelling, shadowing, simulation exercises, and family-centered rounds, which can promote empathetic communication, cultural sensitivity, and reflective practices among clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of game tasks was driven by the goal of fostering prosocial behaviour, competitiveness, problem-solving abilities, conflict resolution, and effective communication skills among participants. Game tasks were selected as a strength-based approach due to their alignment with promoting family support and the joy derived from parent-child play (25). The Matching pairs card game consisted of 52 standard card packs, of which 10 Matching card pairs were selected and used for the game.…”
Section: Stimuli Materialsmentioning
confidence: 99%
“…Approaches to reduce the need for complex services involve the whole range of efective interventions to assess and address parental mental health challenges, the associated children's needs, and whatever other needs the family may have [12,13]. Within approaches to meet families' complex needs, there are specifc interventions to support them to manage the complexity of their needs such as genograms, eco-maps and family journey maps [14], and more general, strengths-based approaches [15]. Unger [16] suggested that family therapists can help clients navigate by making interventions available and culturally relevant and making interventions accessible and integrated and also by working with families to advocate for resources.…”
Section: Introductionmentioning
confidence: 99%